INFLUENCE OF P4K HEALTH EDUCATION THROUGH MBOLO RASA EVENTS ON KNOWLEDGE AND ATTITUDES PREGNANT WOMEN IN COMPLICATED PREGNANCY IN NISA VILLAGE, WOHA SUBDISTRICT, BIMA DISTRICT - Sudarmi Sudarmi; Nahdiayah Hidayati; Imtihanatun Najahah; B. Iin Rumintang (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
Bima Regency recorded that cases of maternal deaths and cases of maternal complications have increased from 2019 to 2021 as the main factors causing deaths of pregnant women. The Childbirth Planning and Complication Prevention (P4K) Program aims to monitor pregnancy towards a safe and secure delivery with the target being all pregnant women. Mbolo Rasa can be a forum for implementing the P4K program by involving families and the community together with midwives in forming an agreement on the community's ability to help plan a safe birth and prepare for complications in pregnant women in Nisa Village, Woha District, Bima Regency. The type of research is pre-experimental with a One Group pre-test post-test research design. The research population was pregnant women in NisaVillage and a sample of 35 respondents. Data analysis found that respondents' knowledge before the intervention was in the sufficient category at 30 (85.7%) and after that the good category was 31 (88.6%). Respondents' attitudes before the intervention were mostly in the negative category, 26 (74.3%) and afterward, the majority were in the positive category, 29 (82.9%). Shows that there is an influence of P4K Health Education through the Mbolo Rasa event on the knowledge and attitudes of pregnant women regarding preventing complications in pregnancy in Nisa Village, Woha District, Bima Regency with a p-value of 0.000 â‰¤ 0.05. Mbolo Rasa can be applied in the P4K Program which can involve all aspects of society.